Hardware-in-the-Loop and Digital Control Techniques Applied to Single-Phase PFC Converters - Lamo-Anuarbe, Paula; de Castro, Ángel; Sanchez, Alberto; Ruiz, Gustavo A.; Azcondo, Francisco J.; Pigazo, Alberto (Electronics, 2022)
Power electronic converters for power factor correction (PFC) play a key role in single-phase electrical power systems, ensuring that the line current waveform complies with the applicable standards and grid codes while regulating the DC voltage. Its verification implies significant complexity and cost, since it requires long simulations to verify its behavior, for around hundreds of milliseconds. The development and test of the controller include nominal, abnormal and fault conditions in which the equipment could be damaged. Hardware-in-the-loop (HIL) is a cost-effective technique that allows the power converter to be replaced by a real-time simulation model, avoiding building prototypes in the early stages for the development and validation of the controller. However, the performance-vs-cost trade-off associated with HIL techniques depends on the mathematical models used for replicating the power converter, the load and the electrical grid, as well as the hardware platform chosen to build it, e.g., microprocessor or FPGA, and the required number of channels and I/O types to test the system. This work reviews state-of-the-art HIL techniques and digital control techniques for single-phase PFC converters.
Keywords: power factor corrector; PFC; digital control; converter; Hardware-in-the-loop; HIL; WOS(2); Scopus